THE EFFECT OF INFLATION, POVERTY, AND INVESTMENT ON SUSTAINABLE DEVELOPMENT IN WEST KALIMANTAN PROVINCE - Sukma Febrianti; Junita Indriyati (Jurnal Ekonomi dan Manajemen, 2020)
The purpose of this study is to examine how big the effect of Inflation, Poverty, and Investment have on Sustainable Development in West Kalimantan Province, partially or simultaneously. Sustainable Development in this study was measured using the Human Development Index (HDI) indicator. This research was conducted because the development of West Kalimantan HDI, when compared to other provinces in Kalimantan, still occupies the lowest position. This research was a quantitative descriptive and used secondary data, the West Kalimantan Financial Report and inflation data. The data used in this study was the annual time series data from 2007-2016. The analysis technique used in this study was Multiple Linear Regression by using SPSS version 25. The partial test results showed that Inflation and Investment had no effect on Sustainable Development in West Kalimantan Province, while Poverty had an effect on Sustainable Development in West Kalimantan Province. Based on the results of the F Test, it showed that Inflation, Poverty and Investment simultaneously had effects on Sustainable Development in the province of West Kalimantan.